It's the first day of school-- forever! - Stine, R. L. (New York : Feiwel and Friends, 2011)
Everything goes wrong for eleven-year-old Artie on his first day at Ardmore Middle School, from the moment his alarm goes off until the next morning, when everything is repeated exactly the same way.
Kirkus Review
Kirkus Review, June 2011
3.3
3-6
3-6
Keywords: First day of school -- Juvenile fiction; Monsters -- Juvenile fiction; Schools -- Juvenile fiction; First day of school -- Fiction; Horror stories; Monsters -- Fiction; Schools -- Fiction; First day of school -- Fiction; Horror fiction; Monsters -- Fiction; School stories; Horror fiction